'Steal me if you can!' The impact of campaign messages on associative issue ownership. (March 2015) - Tresch, Anke; Lefevere, Jonas; Walgrave, Stefaan
Whereas extant work on issue ownership treats voters' issue ownership perceptions as independent variables to explain electoral choice or party behaviour, this article examines whether parties can, by communicating on an issue, turn voters' perceptions of issue ownership to their advantage. In contrast to most previous studies that have focused on competence ownership – measured as a party's capacity to handle an issue – this article analyses the short-term and long-term impact of campaign messages on voters' perceptions of associative ownership, which refers to the voters' spontaneous party–issue association, regardless of whether or not voters consider the party as the most competent at dealing with the issue at hand. Based on an online experimental design in Belgium, we show that parties are unable to steal issues that are associated with another party. However, by communicating on their own issues, parties can reinforce their reputation as an associative owner – but only in the short run and only if their previous ownership reputation is not overly strong.